YOUTH PARTICIPATION IN SAFEGUARDING NATIONAL HISTORICAL HERITAGE - Akhmadalieva Rano Urinboy kizi (Web of Journals Publishing, 2025)
The article explores the crucial role of youth participation in safeguarding national historical heritage. In the context of globalization and rapid modernization, the preservation of cultural and historical values faces increasing challenges. The study emphasizes that young people, as the carriers of national identity and future leaders of society, play a decisive role in maintaining and revitalizing historical consciousness. Through educational initiatives, volunteer programs, and digital heritage projects, youth engagement ensures the continuity of cultural memory and strengthens patriotic values. The research concludes that empowering young generations with historical awareness not only preserves national identity but also contributes to the sustainable development of cultural heritage in the modern era.
Keywords: Youth participation, historical heritage, cultural identity, preservation, innovation, education, national values, sustainability, heritage protection, civic responsibility.